Pronounced Magnetic Bistability in Highly Cooperative Mononuclear [Fe(L npdtz ) 2 (NCX) 2 ] Complexes - Kiehl, Jonathan; Hochdörffer, Tim; Carrella, Luca M; Schünemann, Volker; Nygaard, Mathilde H; Overgaard, Jacob; Rentschler, Eva (Inorganic chemistry, 2022)
Molecular materials that exhibit stimuli-responsive bistability are promising candidates for the development of molecular switches and sensors. We herein report on the coexistence of a wide thermal hysteretic spin crossover (SCO) effect and a thermally inducible metastable high-spin state at low temperatures achieved with the two new complexes [Fe (L ) (NCX) ] (X = S; Se), with L being (2-naphthyl-5-pyridyl-1,2,4-thiadiazole) and X = S ( ) and Se ( ). Pronounced π-π-stacking of the aromatic side residues of the ligands enables strong intermolecular interactions, leading to abrupt SCO properties and broad magnetic hysteresis of 10 K for X = S and 58 K for X = Se. In this paper, we also present the pressure-induced spin-state switching around 0.8 GPa. A pronounced thermally induced excited spin state trapping (TIESST effect) is observed for the highly cooperative SCO compounds, which was experimentally followed by low-temperature single crystal structure analysis (20 K) and temperature-dependent Mössbauer spectroscopy.